Research insights for the classroom (Cambridge, UK, 1996)
This book covers the major issues writing teachers face in setting agendas for teaching writing to nonnative speakers. The book further provides a historical view of the evolution in approaches to the teaching of second language writing and a coherent view of current approaches and issues.
Keywords: English language,Language and languages; Composition and exrcises,Study and teaching,Study and teaching,Foreig speakers